The Contribution of Customer-Centric Strategy, Digital Technology, and Corporate Image to Word of Mouth Through Customer Satisfaction as a Mediating Variable at Insurance Brokerage Companies in Jakarta - Anshori (CV ODIS, 2025)
This study aims to analyze the contribution of customer-centric strategy, digital technology, and corporate image to word of mouth, with customer satisfaction as a mediating variable in insurance brokerage firms in Jakarta. The intense competition in the insurance industry encourages brokers to focus on strategies that enhance customer loyalty and advocacy, particularly through customer satisfaction-driven approaches. This research model examines the relationships between these variables using a quantitative approach. Data were collected through questionnaires distributed to 150 customers of insurance brokerage firms in Jakarta and analyzed using Structural Equation Modeling (SEM). The results show that customer-centric strategy, digital technology, and corporate image significantly contribute to customer satisfaction. Furthermore, satisfaction is proven to be a strong mediating variable influencing word of mouth, indicating that a positive customer experience is crucial in shaping perceptions and the willingness to recommend insurance broker services to others. The implications of this study highlight the importance of building customer-oriented relationships, leveraging digital technology, and strengthening corporate image to enhance satisfaction and drive positive word of mouth. This research may serve as a strategic reference for insurance brokerage firm management in designing more effective, customer-focused marketing policies